Moonlighting in drug metabolism. (2nd January 2021) - Board, Philip G.; Anders, M. W.
Abstract: Drug metabolizing enzymes catalyze the biotransformation of many of drugs and chemicals. The drug metabolizing enzymes are distributed among several evolutionary families and catalyze a range of detoxication reactions, including oxidation/reduction, conjugative, and hydrolytic reactions that serve to detoxify potentially toxic compounds. This detoxication function requires that drug metabolizing enzymes exhibit substrate promiscuity. In addition to their catalytic functions, many drug metabolizing enzymes possess functions unrelated to or in addition to catalysis. Such proteins are termed 'moonlighting proteins' and are defined as proteins with multiple biochemical or biophysical functions that reside in a single protein. This review discusses the diverse moonlighting functions of drug metabolizing enzymes and the roles they play in physiological functions relating to reproduction, vision, cell signaling, cancer, and transport. Further research will likely reveal new examples of moonlighting functions of drug metabolizing enzymes.